Strengths, Weaknesses, Opportunities, and Threats of the Implementation of Moodle in EFL Flipped Classroom Courses (مجلة الواحات للبحوث والدراسات, 2025)
This study investigates the perceptions of undergraduate EFL students from five Algerian universities namely: Batna, Constantine, Khenchela, Oran, and Ouargla regarding the Strengths, Weaknesses, Opportunities, and Threats (SWOT) associated with the use of the Moodle platform as an educational tool for flipped learning. Qualitative research methodology was employed, utilizing focus group which consists of nine undergraduate students as the data collection method. The focus group discussions were structured around the components of SWOT analysis. The findings of this study confirmed the ill- advised decision to choose Moodle as an educational learning. Besides, the discussions highlighted the unexperienced practices in delivering the lessons as far as Flipped Classroom (FC) models are concerned.Keywords: EFL, flipped learning, Moodle platform, SWOT analysis